Successful application and timing of a remote network for intraoperative objective measurements during cochlear implantation surgery. - Yanov, Yuri; Kuzovkov, Vladislav; Sugarova, Serafima; Levin, Sergey; Lilenko, Andrei; Kliachko, Dmitrii (International Journal of Audiology, 2018)
Objective: To determine the time needed to remotely perform a set of intraoperative measurements during cochlear implantation surgery and to compare it to the time needed to perform the same measurements in theatre. Design: Prospective two-arm study comparing a local with a remote measurement setting. Three intraoperative measurements (Impedance Field Telemetry (IFT), evoked compound action potential (ECAP) and evoked stapedius reflex test (eSRT)) were performed with the audiologist present in the operating theatre (i.e. locally) or with the audiologist in his/her office (i.e. remotely). The time needed to complete the measurements, in total and individually, were measured and compared. Study sample: Fifty cochlear implant recipients, aged 0.7-48 years Results: IFT, ECAP and eSRT were performed successfully in all participants. Comparing locally and remotely performed measurements, IFT did not differ significantly, ECAP threshold or slope did not differ significantly differ in any single channel and eSRT measurements did not differ significantly except for in one of six channels. Remote measurements took 8.6 min less to perform than did local measurements (10.04 vs. 18.64 min); a significant difference (p < 0.001). Conclusions: Using a remote network connection for intraoperative objective measurements is an efficient and safe way to perform measurements during cochlear implantation surgery.